Memória transgeracional na qualidade de sementes e na produtividade da soja - Petkowicz, Leandro André (2023)
The growing environment of the mother plant can affect the quality of the seeds generated due to the transgenerational effect, in which the acquired traits can be transmitted to subsequent generations. The aim of this work was to verify the effect of soybean seed vigor and fertility of the production environment on the quality of the seeds generated and on the performance of the subsequent grain crop. For this, in the 2020/2021 harvest, soybean seeds of the M 5917 IPRO® cultivar were classified into three vigor levels (high, medium and very low) and sown in the field in two areas with contrasting levels of soil fertility. After harvesting the seeds, they were standardized to a size of 6.0 mm, forming six lots. The physiological quality of the seeds was evaluated through germination tests, accelerated aging, seedling length, seedling dry mass and emergence speed index in sand. The other seeds were stored, in ambient conditions, for the repetition of the tests after six months of storage and, later, for sowing in the 2021/2022 harvest, to evaluate the performance of the grain crop. The results suggest that the location of soybean seed production influences transgenerational effects on its physiological quality and on the performance of the subsequent grain crop and that more vigorous soybean seeds contribute to the generation of a more productive grain crop.